Reading teaching in Youth and Adult Education: the stimulus equivalence paradigm associated with educational games (Research, Society and Development, 2022)
The stimulus equivalence paradigm has been applied to teach various academic skills, especially in teaching reading procedures. This paradigm is generally used in individualized teaching procedures, so its application in collective contexts is relevant. This study aimed to evaluate a teaching program called Teaching Program to Reading Nominalised Words (PELPS – in Portuguese) applied collectively in Youth and Adult Education (EJA - in Portuguese), in which emerging relationships were tested individually. Nine EJA students aged between 17 and 61 were selected after a reading pre-test. PELPS was conducted in collective teaching sessions. The procedure included teaching conditional relations between dictated and printed words and the construction of words with letters (Constructed Matching to Sample - CRMTS), followed by activities with games (Bingo and scavenger hunt) and tests of emerging relations. After teaching a minimum of nine words, generalization reading tests were performed. Seven of the nine participants performed above 90% in textual reading, picture-to-printed word relations, and printed word-to-picture relations, which configure reading with comprehension. Words with no language difficulties were also read with comprehension in the generalization test. The games positively affected the performance of reading. We concluded that PELPS is a viable and effective program for teaching reading with comprehension in an EJA setting.